The flavokawains: uprising medicinal chalcones - Abu, Nadiah; Ho, Wan Yong; Yeap, Swee Keong; Akhtar, Muhammad Nadeem; Abdullah, Mohd Puad; Omar, Abdul Rahman; Mohammed Alitheen, Noorjahan Banu (BioMed Central, 2013)
Plant-based compounds have been in the spotlight in search of new and promising drugs. Flavokawain A, B and C are naturally occurring chalcones that have been isolated from several medicinal plants; namely the piper methysticum or commercially known as the kava-kava. Multiple researches have been done to evaluate the bioactivities of these compounds. It has been shown that all three flavokawains may hold promising anti-cancer effects. It has also been revealed that both flavokawain A and B are involved in the induction of cell cycle arrest in several cancer cell lines. Nevertheless, flavokawain B was shown to be more effective in treating in vitro cancer cell lines as compared to flavokawain A and C. Flavokawain B also exerts antinociceptive effects as well as anti-inflammation properties. This mini-review attempts to discuss the biological properties of all the flavokawains that have been reported.